Resistance, Resilience, and Recovery from Disasters: Perspectives from Southeast Asia: - Hechanova, Ma. Regina M (Archīum Ateneo, 2020)
The book fills a void by bringing together literature in an under-represented but disaster-prone region, Southeast Asia. It discusses the cultural considerations of those providing mental health and psychosocial support in the region. It highlights the role of education in reducing disaster vulnerability. It presents ways in which workplace organization have sought to enhance employee and organizational resilience in the face of disasters. It discusses how the disaster planning process; including prevention; mitigation; and preparedness efforts; can be integrated with mental health efforts. It features how mental health interventions including psychological first aid; resilience interventions; mindfulness; and art therapy have been carried out. It also discusses the issues of those caring for survivors and describes MHPSS interventions for disaster responders themselves. The book also addresses post-traumatic growth as an outcomes of disaster exposure; concluding by summarizing the challenges and prospects for promoting resistance; resilience; and recovery in SEA.